Review of construction and demolition waste management in China and USA. (15th June 2020) - Aslam, Muhammad Shahzad; Huang, Beijia; Cui, Lifeng
Abstract: It has been observed that the massive urbanization has boosted up infinite construction in the developed as well as developing countries. The construction and demolition waste has been correspondingly increased enormously which results in nasty and fatal impacts on urban sustainability and survival in the term of economic values and environmental safety. Considering construction and demolition waste management (CDWM) in the USA and China and its comparison has not been discussed, this study explores some research questions to fill such gaps: What are the existing CDWM policies and regulations in these two countries? What is the market mode for CDWM? What are the key challenges of CDWM? What are the CDWM contribution and limitations toward circular economy? What are the lessons that must be exemplary for the two economies through mutual learning? Our results show that the CD waste generation and its management are influenced by several factors including population, urbanization, gross domestic product (GDP), and CDWM regulatory measures. The USA has more developed CDWM system. Whereas, China is a growing economy and it has some management deficiencies in the construction industry. Key suggestions for improving CDWM include: i. Government supervision along with an economic incentive approach, ii. Interaction between Stakeholders, iii. Mutual coordination among operational departments, iv. Audit and inspection setup, and v. Continuous development and integration of emerging technologies. Graphical abstract: Image 1 Highlights: Review policies and market mode of construction and demolition waste management in the USA and China. Identify challenges of construction and demolition waste management in United States and China. Conduct comparative study between the United States and China and conclude mutual learning suggestions. Propose recommendations to improve construction and demolition waste management.